A method for forming a SiC-based composite coating on the surface of a 3D-printed complex ceramic structure
Patent Information
- Application Number
- CN202611029884.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-27
Smart Images

Figure CN122977868A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic material surface coating preparation technology, specifically to a method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing. Background Technology
[0002] Silicon carbide ceramics, due to their high hardness, good wear resistance, corrosion resistance, oxidation resistance, and high-temperature resistance, are widely used in high-temperature structural components, wear-resistant parts, thermal protection components, filter carriers, and functional structural components in extreme service environments. With the increasing demand for integrated structural and functional designs, ceramic components with complex three-dimensional geometries have high application value in fields such as high-temperature insulation, filtration, lightweight load-bearing, complex flow channels, and extreme environment protection.
[0003] 3D printing technology can overcome the limitations of traditional mold forming on structural complexity, making it suitable for fabricating ceramic components with complex geometric features. However, SiC ceramic materials have strong covalent bonds, low sintering reactivity, and are difficult to control in terms of slurry system stability. When directly using SiC ceramic slurry for 3D printing of complex structures, problems often arise regarding slurry solid content, rheology, forming stability, debinding and sintering shrinkage, dimensional accuracy, and yield. In particular, for complex three-dimensional oxide ceramic structures, direct printing of SiC ceramics often places high demands on powder, resin systems, printing equipment, and sintering processes.
[0004] In contrast, oxide ceramic materials such as alumina, zirconium oxide, and mullite have relatively mature 3D printing and sintering processes, enabling the stable acquisition of complex ceramic frameworks. If a complex structural framework is first prepared using easily 3D-printable ceramic materials, and then a SiC-based functional coating is formed on the surface of this framework, the forming of complex geometries can be separated from the SiC functionalization process, thereby reducing the difficulty of directly 3D printing complex SiC structures.
[0005] Existing methods for preparing SiC coatings on ceramic surfaces mainly include chemical vapor deposition (CVD), physical vapor deposition (PVD), sputtering, spraying, brushing, embedding / siliconizing, and slurry coating. CVD and PVD can produce relatively uniform coatings, but they are costly, have low deposition rates, and are less efficient at forming thicker coatings. Furthermore, their coating coverage efficiency and thickness control are limited for complex three-dimensional ceramic structures. Spraying and brushing are relatively simple processes, but their adaptability to complex geometries is limited. Embedding or siliconizing processes involve high-temperature reactions and diffusion, making process control complex and potentially introducing free silicon or other impurity phases. In addition, some existing technologies have proposed using 3D-printed resin templates, organic templates, or carbon-based porous frameworks combined with SiC-based slurries and high-temperature treatment processes to prepare monolithic SiC porous ceramic materials. These methods are primarily aimed at preparing SiC porous ceramic materials or combustion media substrates, rather than constructing SiC-based composite coatings on the surface of sintered 3D-printed oxide complex ceramic structures.
[0006] Therefore, for 3D printed oxide complex ceramic structures that have undergone debinding and sintering, it is still necessary to develop a method to form SiC-based composite coatings on their surfaces. Summary of the Invention
[0007] To address the shortcomings of the aforementioned background technologies, this invention primarily solves the problems of high difficulty in directly 3D printing complex SiC structures, insufficient adaptability of traditional SiC coating preparation methods to sintered 3D-printed complex oxide ceramic structures, and inconvenience in coating thickness control. This invention provides a method for forming a SiC-based composite coating on the surface of a 3D-printed complex ceramic structure. This method should use the sintered oxide ceramic structure as the coating carrier, achieving SiC-based surface functionalization while maintaining its original complex structural morphology; it should also enable the SiC-based composite ceramic slurry to effectively cover the surface of the complex ceramic structure, and effectively remove excess slurry after coating to reduce slurry accumulation and structural pore blockage. This method should also have the advantages of relatively simple slurry preparation, good adaptability to complex structures, easy control of coating thickness, and low equipment requirements.
[0008] The first objective of this invention is to provide a method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing, comprising the following steps: A SiC-based composite ceramic slurry is prepared by mixing coarse SiC powder, fine SiC powder, inorganic ceramic components, silicon powder, organic binder, dispersant, ethanol, and water. SiC-based composite ceramic slurry is applied to the surface of a ceramic skeleton by one or more methods such as impregnation, coating, and impregnation, dried, and then sintered in an inert atmosphere to form a continuous SiC-based composite coating on the surface of the ceramic skeleton. Among them, the ceramic skeleton is a 3D printed oxide complex ceramic structure skeleton; The coarse SiC powder has a particle size of 10~50μm, and the fine SiC powder has a particle size of 0.5~10μm.
[0009] Preferably, the inorganic ceramic component is one or more of Al2O3 micro powder and SiO2 powder; The organic binder is phenolic resin and / or polyvinyl alcohol.
[0010] Preferably, the SiC-based composite ceramic slurry comprises, by weight, the following components: 5-18 parts coarse SiC powder, 3-12 parts fine SiC powder, 0-8 parts Al2O3 micro powder, 0.1-1.5 parts SiO2 powder, 1-5 parts silicon powder; 1-4 parts phenolic resin; 0.5-3 parts 10 wt% polyvinyl alcohol solution, 0.05-0.3 parts dispersant, 5-15 parts water, and 10-25 parts ethanol.
[0011] Preferably, in preparing the SiC-based composite ceramic slurry, coarse SiC powder, fine SiC powder, silicon powder, and SiO2 powder are added to an alcohol-water mixed solvent composed of water and ethanol. After adding a dispersant, the mixture is pre-dispersed. Then, phenolic resin and polyvinyl alcohol solution are added, and the mixture is ball-milled at 200-500 r / min for 10-20 hours to ensure uniform dispersion of the components, thereby obtaining the SiC-based composite ceramic slurry.
[0012] Preferably, the dispersant is a polycarboxylate.
[0013] Preferably, when sintering is performed under an inert atmosphere, the sintering temperature is 1700~1850℃ and the holding time is 2~6 hours.
[0014] Preferably, the drying temperature is 100~150℃.
[0015] Preferably, the 3D printed oxide complex ceramic structure skeleton is an alumina ceramic skeleton, a zirconia ceramic skeleton, a mullite ceramic skeleton, a cordierite ceramic skeleton, or a silicon oxide-based ceramic skeleton; the 3D printed oxide complex ceramic structure skeleton is a 3D printed oxide complex ceramic structure skeleton after debinding and sintering treatment.
[0016] The second objective of this invention is to provide a SiC-based composite coating formed on the surface of a complex ceramic structure in 3D printing.
[0017] A third objective of this invention is to provide an application of SiC-based composite coatings in functional structural components in extreme service environments.
[0018] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a method for forming a SiC-based composite coating on the surface of a complex ceramic structure using 3D printing. This method separates the forming of the complex oxide ceramic structure from the preparation of the SiC functional coating. The complex oxide ceramic structure framework is first prepared using 3D printing technology and then debonded and sintered. A SiC-based composite coating is then formed on its surface, avoiding the problems of complex slurry systems, high sintering difficulty, uncontrollable dimensional shrinkage, and insufficient forming stability encountered when directly 3D printing complex SiC structures.
[0019] This invention uses SiC-based composite ceramic slurry to impregnate or coat sintered oxide complex ceramic frameworks, enabling the slurry to cover the surface of the complex ceramic framework. Compared with simple external surface spraying or local brushing methods, it has better adaptability to complex structures.
[0020] This invention employs a coarse-fine SiC powder gradation. By adjusting the ratio of coarse-fine SiC powder, the solvent ratio, and the content of organic binder, the fluidity, coating state, and integrity of the pre-coating layer after drying of the slurry are controlled.
[0021] This invention includes a step to remove excess slurry after slurry coating. By using natural dripping, slight vibration, rotary slurry discharge, or compressed gas purging, the accumulation of slurry in localized areas of complex structures is reduced, thereby reducing the risk of pore blockage and improving the uniformity of the pre-coating.
[0022] The present invention can control the thickness of SiC-based composite coatings by adjusting the solid content of the slurry, the ratio of coarse to fine SiC powder, the slurry discharge method, and the number of slurry covering, discharge, and drying processes. Attached Figure Description
[0023] Figure 1 This is a flowchart of the method for forming a SiC-based composite coating on the surface of a 3D-printed oxide complex ceramic structure after degreasing and sintering treatment, according to the present invention. Figure 2 The image shows a complex alumina lattice structure prepared by 3D printing and then subjected to debinding and sintering. Figure 3 The image shows a sample obtained after applying coarse and fine SiC graded composite ceramic slurry to the surface of a complex alumina lattice structure that has been degreased and sintered, and then drying it at 120°C in Example 1. (a) The sample was coated with slurry, excess slurry was removed, and the sample was dried once. (b) The sample was coated with slurry, excess slurry was removed, and the sample was dried three times. Figure 4 The image shows a photograph (left) of the sample obtained in Comparative Example 1, and a magnified view (right). Detailed Implementation
[0024] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings. However, the embodiments described are not intended to limit the present invention.
[0025] This invention addresses existing methods for preparing SiC coatings on ceramic surfaces, which mainly include chemical vapor deposition (CVD), physical vapor deposition (PVD), sputtering, spraying, brushing, embedding / siliconizing, and slurry coating. CVD and PVD can achieve relatively uniform coatings, but they suffer from high equipment costs, low deposition rates, and low efficiency in forming thicker coatings. Furthermore, their coating coverage efficiency and thickness control are limited for complex three-dimensional ceramic structures. Spraying and brushing are relatively simple processes, but their adaptability to complex geometries is limited. Embedding or siliconizing processes involve high-temperature reactions and diffusion, making process control complex and potentially introducing free silicon or other impurity phases. In addition, some existing technologies have proposed using 3D-printed resin templates, organic templates, or carbon-based porous frameworks combined with SiC-based slurries and high-temperature treatment processes to prepare monolithic SiC porous ceramic materials. These methods primarily target the preparation of SiC porous ceramic materials or combustion media bodies, rather than the construction of SiC-based composite coatings on the surface of sintered 3D-printed oxide complex ceramic structures.
[0026] The present invention aims to provide a method for forming a SiC-based composite coating on the surface of a 3D-printed complex ceramic structure. The method includes providing a 3D-printed oxide complex ceramic structure skeleton after debinding and sintering, wherein the oxide complex ceramic structure skeleton is retained as a coating carrier during subsequent sintering; preparing a SiC-based composite ceramic slurry comprising coarse SiC powder, fine SiC powder, inorganic ceramic components, silicon powder, organic binder, dispersant, and an alcohol-water mixed solvent; applying the SiC-based composite ceramic slurry to the surface of the 3D-printed oxide complex ceramic structure skeleton by impregnation, coating, or a combination of impregnation and coating; removing excess slurry adhering to the surface of the oxide complex ceramic structure skeleton; forming a SiC-based pre-coating after drying, and repeating the slurry application, excess slurry removal, and drying process according to the target coating thickness; and subsequently sintering under an inert atmosphere, allowing the SiC powder, inorganic ceramic components, and silicon powder in the SiC-based composite ceramic slurry to adhere to the surface of the 3D-printed complex ceramic structure. The surface of a printed complex oxide ceramic structure skeleton is sintered and solidified to form a SiC-based composite coating covering the surface of the complex oxide ceramic structure skeleton. This invention separates the forming of the complex oxide ceramic structure from the preparation of the SiC-based functional coating, avoiding the problems of complex slurry systems, high sintering difficulty, and difficulty in dimensional control when directly 3D printing complex SiC structures. Furthermore, the coating thickness can be controlled by adjusting the slurry solid content, the gradation of coarse and fine SiC powders, the slurry discharge method, and the number of repeated processing steps. This invention is suitable for the surface functionalization of 3D printed complex oxide ceramic structures.
[0027] To achieve the above objectives, the first aspect of the present invention provides a method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing, comprising the following steps: A SiC-based composite ceramic slurry is prepared by mixing coarse SiC powder, fine SiC powder, inorganic ceramic components, silicon powder, organic binder, dispersant, ethanol, and water. SiC-based composite ceramic slurry is applied to the surface of a ceramic skeleton by one or more methods such as impregnation, coating, and impregnation, dried, and then sintered in an inert atmosphere to form a continuous SiC-based composite coating on the surface of the ceramic skeleton. Among them, the ceramic skeleton is a 3D printed oxide complex ceramic structure skeleton; The coarse SiC powder has a particle size of 10~50μm, and the fine SiC powder has a particle size of 0.5~10 μm; This invention employs a coarse-fine SiC powder gradation. By adjusting the ratio of coarse-fine SiC powder, the solvent ratio, and the content of organic binder, the fluidity, coating state, and integrity of the pre-coating layer after drying of the slurry are controlled.
[0028] The inorganic ceramic component is one or more of Al2O3 micro powder and SiO2 powder; The organic binder is phenolic resin and / or polyvinyl alcohol.
[0029] The SiC-based composite ceramic slurry comprises, by weight, the following parts: 5-18 parts coarse SiC powder, 3-12 parts fine SiC powder, 0-8 parts Al2O3 micro powder, 0.1-1.5 parts SiO2 powder, 1-5 parts silicon powder; 1-4 parts phenolic resin; 0.5-3 parts 10 wt% polyvinyl alcohol solution, 0.05-0.3 parts dispersant, 5-15 parts water, and 10-25 parts ethanol.
[0030] In preparing SiC-based composite ceramic slurry, coarse SiC powder, fine SiC powder, silicon powder, and SiO2 powder are added to an alcohol-water mixed solvent composed of water and ethanol. After adding a dispersant, the mixture is pre-dispersed. Then, phenolic resin and polyvinyl alcohol solution are added, and the mixture is ball-milled at 200-500 r / min for 10-20 hours to ensure uniform dispersion of the components, thus obtaining the SiC-based composite ceramic slurry.
[0031] The dispersant is a polycarboxylate.
[0032] When sintering in an inert atmosphere, the sintering temperature is 1700~1850℃ and the holding time is 2~6 hours.
[0033] The drying temperature is 100~150℃.
[0034] The 3D printed oxide complex ceramic structure framework is an alumina ceramic framework, a zirconia ceramic framework, a mullite ceramic framework, a cordierite ceramic framework, or a silicon oxide-based ceramic framework; the 3D printed oxide complex ceramic structure framework is a 3D printed oxide complex ceramic structure framework after debinding and sintering treatment.
[0035] An exemplary method for forming a SiC-based composite coating on the surface of a 3D-printed oxide complex ceramic structure after degreasing and sintering treatment, see [link to relevant documentation]. Figure 1 As shown, it includes the following steps: (1) Provide a 3D printed complex ceramic structure skeleton after debinding and sintering treatment, see Figure 2 As shown; (2) Prepare a SiC-based composite ceramic slurry comprising coarse SiC powder, fine SiC powder, inorganic ceramic components, silicon powder, organic binder, dispersant and alcohol-water mixed solvent; wherein, coarse SiC powder is used to form the main particle skeleton of the pre-coating, fine SiC powder is used to fill the gaps between coarse SiC powder, inorganic ceramic components and silicon powder are used to promote the consolidation between coating particles and between the coating and the surface of the oxide ceramic skeleton during sintering, organic binder is used to improve the slurry coating stability and the integrity of the pre-coating after drying, dispersant is used to improve the dispersion state of inorganic particles in alcohol-water mixed solvent, and alcohol-water mixed solvent is used to adjust the wettability, flowability and drying behavior of the slurry.
[0036] (3) Applying slurry to the surface of a complex ceramic structure skeleton by impregnation, coating or a combination thereof; (4) Remove excess slurry by natural dripping, slight vibration, rotary slurry discharge, or gas purging; (5) Drying is performed to form a SiC-based pre-coating; (6) Repeat steps (3) to (5) according to the target coating thickness; (7) Sintering under an inert atmosphere to form a SiC-based composite coating.
[0037] The 3D-printed complex ceramic structure skeleton has three-dimensional complex geometric features formed by 3D printing.
[0038] The SiC powder includes coarse SiC powder and fine SiC powder. By grading the coarse and fine SiC powders, the packing density of ceramic particles in the slurry is increased on the one hand, and the slurry flowability, coating thickness, and integrity of the pre-coating layer after drying are adjusted on the other hand.
[0039] The organic binder includes phenolic resin, polyvinyl alcohol, or a combination thereof. Phenolic resin and polyvinyl alcohol are primarily used to improve the stability of the slurry coating, enhance the integrity of the pre-coated layer after drying, and improve its resistance to powdering.
[0040] The alcohol-water mixed solvent includes water and ethanol. By adjusting the ratio of water to ethanol, the wettability of the slurry on the ceramic skeleton surface, the drying speed, and the uniformity of coating can be improved.
[0041] After the slurry is applied, excess slurry on the surface of the complex ceramic structure skeleton is removed by natural dripping, slight vibration, rotational slurry discharge, compressed gas purging, or a combination thereof, in order to reduce the accumulation of slurry at structural corners, nodes, and local areas.
[0042] Depending on the target pre-coating coverage and coating thickness, the total number of times the slurry is applied, excess slurry is removed, and drying is performed is 1 to 5.
[0043] In this invention, the 3D-printed alumina complex lattice structure is an alumina ceramic part formed by DLP photopolymerization 3D printing. It can be obtained through the following conventional process: alumina ceramic photopolymerization slurry is formed by DLP 3D printing to obtain an alumina ceramic preform; subsequently, the alumina ceramic preform is cleaned, dried, degreased, and sintered to obtain an alumina ceramic matrix.
[0044] The solid content of alumina powder in the alumina ceramic photocurable slurry is 40-65 vol.%, preferably 50-58 vol.%; the DLP printing layer thickness is 20-150 μm, preferably 25-100 μm; the single-layer exposure time is 1-20 s, preferably 2-10 s; and the sintering temperature is 1450-1700℃, preferably 1550-1650℃.
[0045] The alumina ceramic photocurable slurry comprises, by weight: 80-85 parts of α-Al2O3 powder, 12-18 parts of acrylate photosensitive resin, 1-3 parts of dispersant, 0.1-0.5 parts of photoinitiator, and 0.1-0.5 parts of defoamer; the acrylate photosensitive resin includes one or more of 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, and epoxy acrylate.
[0046] In the following specific embodiments, the alumina ceramic photocurable slurry comprises, by weight, 82.0 parts of α-Al₂O₃ powder, 12.0 parts of 1,6-hexanediol diacrylate, 3.8 parts of bisphenol A epoxy acrylate, 1.7 parts of BYK-111 dispersant, 0.3 parts of 2,4,6-trimethylbenzoyl diphenylphosphine oxide, and 0.2 parts of BYK-066N defoamer. When the alumina ceramic photocurable slurry is formed by DLP 3D printing, a 405 nm light source is used for DLP printing, the printed layer thickness is 50 μm, the single-layer exposure time is 5 s, and after segmented degreasing, it is sintered at 1600℃ for 3 hours. (See [reference needed]). Figure 2 The diagram shows a schematic of a complex lattice structure of 3D-printed alumina.
[0047] A second aspect of the present invention provides a SiC-based composite coating formed on the surface of a complex ceramic structure in 3D printing.
[0048] A third aspect of the present invention provides an application of a SiC-based composite coating in functional structural components in extreme service environments.
[0049] It should be noted that, unless otherwise specified, the experimental methods used in this invention are all conventional methods; and the reagents and materials used, unless otherwise specified, are all commercially available.
[0050] Example 1 SiC-based pre-coatings and composite coatings were formed on the surface of 3D-printed alumina complex lattice structures after degreasing and sintering. (See also...) Figure 1 As shown, it includes: (1) Weigh each material according to the formula of coarse SiC powder, fine SiC powder, Si powder, phenolic resin, SiO2 powder, PVA solution, dispersant, water and ethanol. The amount of each component is as follows: 11 g of coarse SiC powder (20~45 μm), 6 g of fine SiC powder (1~5 μm), 3.8 g of Si powder, 0.2 g of SiO2 powder, 2.8 g of phenolic resin, 2 g of 10 wt% PVA solution, 0.2 g of polycarboxylate dispersant, 9 g of water and 15 g of ethanol.
[0051] The weighed coarse SiC powder, fine SiC powder, Si powder and SiO2 powder were added to an alcohol-water mixed solvent composed of water and ethanol, and a dispersant was added for pre-dispersion. Then, phenolic resin and PVA solution were added, and the mixture was ball-milled at 300 r / min for 12 hours to ensure uniform dispersion of each component, thus obtaining a coarse and fine SiC graded composite ceramic slurry.
[0052] (2) Using a 3D-printed alumina complex ceramic structure framework after degreasing and sintering (see Figure 2 The alumina complex lattice structure skeleton is used as the substrate, and it is retained as a coating carrier in subsequent processing. The coarse and fine SiC graded composite ceramic slurry obtained in step (1) is coated on the surface of the 3D printed alumina complex ceramic structure skeleton, so that the slurry covers the surface of the complex ceramic structure skeleton.
[0053] (3) After coating, excess slurry on the surface of the complex lattice structure is removed by natural dripping and slight vibration to reduce slurry accumulation at nodes, corners, and local areas. The sample is then dried at 120°C to form a SiC-based pre-coating covering the surface of the alumina complex lattice structure skeleton. Samples were prepared after slurry coating, removal of excess slurry, and drying once and three times, respectively. Each treatment included slurry coating, natural dripping and slight vibration to remove excess slurry, and drying at 120°C. The diameter of the rods in the 3D printed alumina complex lattice structure skeleton before coating was approximately 1.5 mm; after one slurry coating, slurry removal, and drying treatment, the outer diameter of the rods was approximately 1.8 mm; after three slurry coating, slurry removal, and drying treatments, the outer diameter of the rods was approximately 2.5 mm. Based on the change in the outer diameter of the rods, the apparent single-sided thickness of the SiC-based pre-coating formed after one treatment was approximately 0.15 mm, and the apparent single-sided thickness of the SiC-based pre-coating formed after three treatments was approximately 0.50 mm. The above results indicate that the coverage and apparent thickness of the SiC-based pre-coating on the surface of the lattice rod can be adjusted by increasing the number of slurry covering, slurry removal, and drying treatments. The samples obtained after one and three treatments correspond to... Figure 3 (a) and Figure 3 (b).
[0054] (4) The 3D-printed alumina complex ceramic structure skeleton with SiC-based pre-coating obtained in step (3) is placed in a sintering furnace for sintering. The sintering atmosphere is Ar atmosphere, the sintering temperature is 1800℃, the holding time is 4 hours, and then it is cooled with the furnace. After sintering, the SiC powder and inorganic components in the slurry are solidified on the surface of the complex ceramic structure skeleton to form a SiC-based composite coating.
[0055] Example 2 Same as Example 1, except that, In step (1), each material is weighed according to the formula of coarse SiC powder, fine SiC powder, Si powder, phenolic resin, SiO2 powder, PVA solution, dispersant, water and ethanol. The amount of each component is as follows: 5g of coarse SiC powder (20~45 μm), 3g of fine SiC powder (1~5 μm), 1g of Si powder, 0.1g of SiO2 powder, 1g of phenolic resin, 0.5g of 10 wt% PVA solution, 0.05g of polycarboxylate dispersant, 5g of water and 10g of ethanol.
[0056] In step (4), the sintering temperature is 1700℃ and the holding time is 6 hours.
[0057] Example 3 Same as Example 1, except that, In step (1), each material is weighed according to the formula of coarse SiC powder, fine SiC powder, Si powder, phenolic resin, SiO2 powder, PVA solution, dispersant, water and ethanol. The amount of each component is as follows: 18g of coarse SiC powder (20~45 μm), 12g of fine SiC powder (1~5 μm), 5g of Si powder, 1.5g of SiO2 powder, 4g of phenolic resin, 3g of 10 wt% PVA solution, 0.3g of polycarboxylate dispersant, 15g of water and 25g of ethanol.
[0058] In step (4), the sintering temperature is 1850℃ and the holding time is 2 hours.
[0059] Comparative Example 1 Preparation of SiC-based composite ceramic slurries and coatings without the addition of fine SiC powder, including: To illustrate the role of fine SiC powder in SiC-based composite ceramic slurry, a comparative example without fine SiC powder was set up. Except for the different particle size distribution of SiC powder, the types of other components, the total amount of SiC powder, the slurry preparation method, the coating method, the method of removing excess slurry, the drying conditions, and the sintering conditions in this comparative example were all the same as in Example 1.
[0060] (1) In this comparative example, each material was weighed according to the formula of coarse SiC powder, silicon powder, SiO2 powder, phenolic resin, PVA solution, dispersant, water and ethanol. The amounts of each component are as follows: 17 g of coarse SiC powder (20-45 μm), 3.8 g of Si powder, 0.2 g of SiO2 powder, 2.8 g of phenolic resin, 2 g of 10 wt% PVA solution, 0.2 g of polycarboxylate dispersant, 9 g of water and 15 g of ethanol. Fine SiC powder was not added in this comparative example. The weighed coarse SiC powder, silicon powder and SiO2 powder were added to an alcohol-water mixed solvent composed of water and ethanol, and pre-dispersed after adding polycarboxylate dispersant; then phenolic resin and PVA solution were added, and ball milling was carried out at 300 r / min for 12 h to make the components uniformly mixed, so as to obtain a SiC-based composite ceramic slurry without fine SiC powder.
[0061] (2) Using a 3D-printed alumina complex lattice structure framework after degreasing and sintering as the substrate, the above-mentioned slurry is coated onto the surface of the alumina complex lattice structure framework, so that the slurry covers the accessible surface of the alumina complex lattice structure framework. After coating, excess slurry on the surface of the complex lattice structure is removed by natural dripping and slight vibration. Then, the sample is dried at 120°C to form a SiC-based pre-coating. The slurry coating, excess slurry removal and drying processes are repeated as needed.
[0062] (3) The dried sample was placed in a sintering furnace and sintered under an Ar atmosphere at a temperature of 1800℃ for 4 h. The sample was then cooled in the furnace to obtain the sample of Comparative Example 1.
[0063] (4) The samples obtained in Example 1 and Comparative Example 1 were compared and evaluated. The results showed that, compared with Example 1, the static stability of the slurry obtained in Comparative Example 1 did not change significantly, and no obvious stratification or severe sedimentation occurred after static standing; however, the viscosity of the slurry increased, and the fluidity and spreading ability on the complex lattice structure surface of alumina decreased, resulting in poorer uniformity of slurry coverage during the coating process. After one slurry coating, natural dripping, and slight vibration to remove excess slurry, and drying at 120°C, the outer diameter of the lattice rods in the Comparative Example 1 sample was approximately 2.1 mm, which was higher than the outer diameter of approximately 1.8 mm of the rods after one treatment in Example 1. After drying, it was observed that the SiC-based pre-coating formed in Comparative Example 1 had slight cracking, indicating that the integrity of the pre-coating after drying was lower than that in Example 1.
[0064] (5) The above results indicate that fine SiC powder does not exist solely as a filler component in SiC-based composite ceramic slurry, but rather works in conjunction with coarse SiC powder to play a role in particle gradation. Coarse SiC powder mainly forms the particle skeleton of the pre-coating, while fine SiC powder fills the gaps between coarse SiC particles, improving particle packing and slurry flow and coverage behavior. When fine SiC powder is lacking, the gaps between coarse SiC particles are not adequately filled, leading to uneven coverage and localized accumulation during slurry coating. Uneven stress release within the pre-coating during drying can result in slight cracking. Therefore, coarse and fine SiC powders have a synergistic gradation effect, which is beneficial for improving the slurry's coverage of the complex lattice structure of 3D-printed alumina and enhancing the integrity of the SiC-based pre-coating after drying.
[0065] To illustrate the relevant properties of the SiC-based composite coating formed on the surface of a complex ceramic structure in 3D printing provided by this invention, the accompanying drawings are provided.
[0066] See Figure 4 As shown, Comparative Example 1 uses a SiC-based composite ceramic slurry without fine SiC powder. After one slurry coating, natural dripping, and slight vibration to remove excess slurry, and drying at 120°C, local cracks can be observed on the surface of the formed SiC-based pre-coated layer, indicating that the surface integrity of the pre-coated layer is poor.
[0067] In Comparative Example 1, the lack of fine SiC powder filling the gaps between coarse SiC particles resulted in reduced particle packing uniformity within the pre-coating, leading to variations in local slurry layer thickness and particle distribution. During drying, the stress generated by solvent evaporation and organic binder shrinkage was difficult to release uniformly, causing stress concentration and crack formation in localized areas. In contrast, Example 1 used a coarse and fine SiC powder gradation. The fine SiC powder filled the gaps between coarse SiC particles, improving particle packing and pre-coating structural uniformity, thereby reducing the tendency for localized cracking during drying and enhancing the integrity of the SiC-based pre-coating.
[0068] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing, characterized in that, Includes the following steps: A SiC-based composite ceramic slurry is prepared by mixing coarse SiC powder, fine SiC powder, inorganic ceramic components, silicon powder, organic binder, dispersant, ethanol, and water. SiC-based composite ceramic slurry is applied to the surface of a ceramic skeleton by one or more methods such as impregnation, coating, and impregnation, dried, and then sintered in an inert atmosphere to form a continuous SiC-based composite coating on the surface of the ceramic skeleton. Among them, the ceramic skeleton is a 3D printed oxide complex ceramic structure skeleton; The coarse SiC powder has a particle size of 10~50μm, and the fine SiC powder has a particle size of 0.5~10μm.
2. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 1, characterized in that, The inorganic ceramic component is one or more of Al2O3 micro powder and SiO2 powder; The organic binder is phenolic resin and / or polyvinyl alcohol.
3. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 2, characterized in that, The SiC-based composite ceramic slurry comprises, by weight, the following parts: 5-18 parts coarse SiC powder, 3-12 parts fine SiC powder, 0-8 parts Al2O3 micro powder, 0.1-1.5 parts SiO2 powder, 1-5 parts silicon powder; 1-4 parts phenolic resin; 0.5-3 parts 10 wt% polyvinyl alcohol solution, 0.05-0.3 parts dispersant, 5-15 parts water, and 10-25 parts ethanol.
4. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 3, characterized in that, In preparing SiC-based composite ceramic slurry, coarse SiC powder, fine SiC powder, silicon powder, and SiO2 powder are added to an alcohol-water mixed solvent composed of water and ethanol. After adding a dispersant, the mixture is pre-dispersed. Then, phenolic resin and polyvinyl alcohol solution are added, and the mixture is ball-milled at 200-500 r / min for 10-20 hours to ensure uniform dispersion of the components, thus obtaining the SiC-based composite ceramic slurry.
5. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 1, characterized in that, The dispersant is a polycarboxylate.
6. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 1, characterized in that, When sintering in an inert atmosphere, the sintering temperature is 1700~1850℃ and the holding time is 2~6 hours.
7. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 1, characterized in that, The drying temperature is 100~150℃.
8. The method for forming a SiC-based composite coating on the surface of a complex ceramic structure in 3D printing according to claim 1, characterized in that, The 3D printed oxide complex ceramic structure framework is an alumina ceramic framework, a zirconia ceramic framework, a mullite ceramic framework, a cordierite ceramic framework, or a silicon oxide-based ceramic framework; the 3D printed oxide complex ceramic structure framework is a 3D printed oxide complex ceramic structure framework after debinding and sintering treatment.
9. A SiC-based composite coating formed on the surface of a complex ceramic structure in 3D printing, obtained by the method of any one of claims 1 to 8.
10. The application of the SiC-based composite coating of claim 9 in functional structural components in extreme service environments.